Connecting Core Concepts with Everyday Chemistry - Miraflores-Barizo, Ophelia (My University, 1995)
The rationale for this project is based on the recognition that chemistry courses tend to be taught too much from a theoretical standpoint, with little reference to everyday life. This is one of the reasons that a majority of students think that chemistry is difficult, boring, tedious, and uninteresting (Worthy, 1982). If they have the choice, many students would rather not take a chemistry course, and if they do, it will probably be their last course in Chemistry.
It is the intent of the Ontario Curriculum Guidelines to provide some science-technology-society connections. The aim of this project is to provide supplemental science-technology society connections, and selected concrete examples of practical, everyday chemistry for teachers, so that they may enrich their classes, motivate their students, and put theory into an appropriate context. If classes are more interesting and relevant to the world of the students, then more students could be motivated to take chemistry courses and consider continuing to more advanced classes. A second purpose for this project is to stimulate a typical non-science student's interest in chemistry and science. It is even more necessary to motivate these students by providing interesting connections with the real world and suitable applications of theory and principles. These connections with the real world are important for such students, so that they will be better able to make informed decisions as scientifically literate citizens, managers, or politicians, not only for themselves, but for the benefit of society as a whole.
To accomplish the aims of this project, two or three short hand-outs of practical everyday chemistry were prepared for each of the core topics in the Grade 11 (SCH 3A) and Chemistry OAC (SCH OA) courses. A few of the examples included Dental Chemistry, Culinary Chemistry, Insect Pheromones, and Teflon.
Results of the survey taken from chemistry teachers showed that these hand-outs would better motivate students to study chemistry. Teachers think it is useful for their classes. They would like a compilation of these examples, if one were to be made available.
Keywords: connecting, core, concepts, chemistry, everyday, theory, applications